Bibliotherapy in the UK: historical development and future directions - Sarah McNicol; Liz Brewster (Informatio)
This article discusses three contrasting models of bibliotherapy which have developed in the UK over the last two decades. Building on the earlier history of bibliotherapy, each of these models aim to provide access to selected texts which it is hoped will have a positive effect on a reader’s mental health. The most widespread schemes draw from medical and healthcare knowledge to provide self-help resources for diagnosed mental health conditions. Alongside this, there are schemes shaped by literary and educational experts that focus on facilitating access to fiction and poetry (often with an emphasis on «quality fiction»), usually through group reading. In addition, there is a third model which has, thus far, received less widespread recognition. Drawing on key notions from social care and community development, this model places greater emphasis on the participants in bibliotherapy than on the resources that are used. This «person-centred» model takes a more inclusive interpretation of what we mean by a bibliotherapy «text» and has the potential for the future development of UK bibliotherapy through widening the audiences who want to engage with, and can benefit from, bibliotherapy.